2022
DOI: 10.3390/medicina58091295
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Glucose Disturbances in Premature Infants

Abstract: Background and Objectives: There are limited data regarding the incidence and risk factors for hypoglycemia, hyperglycemia, and unstable glycemia in preterm infants. The aim of the present study was to determine the incidence and risk factors associated with neonatal hypoglycemia, hyperglycemia, and unstable glycemia in preterm infants during the first seven days of life. Materials and Methods: This prospective study included preterm infants <37 weeks of gestation, admitted to the Neonatal Intensive Care Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Although the reason for this relationship is unclear, females may be more sensitive to in-utero exposure to increased glucose levels than males (14, 15). Our observation is consistent with Ahel et al, who found in a recent study that the chances of developing hypoglycemia are increased three times by females compared to males gender (16).…”
Section: Discussionsupporting
confidence: 94%
“…Although the reason for this relationship is unclear, females may be more sensitive to in-utero exposure to increased glucose levels than males (14, 15). Our observation is consistent with Ahel et al, who found in a recent study that the chances of developing hypoglycemia are increased three times by females compared to males gender (16).…”
Section: Discussionsupporting
confidence: 94%
“…Among 66 infants 48.5% were males while 51.5 % were females; 16 (24.24%) were gestational age <34 weeks, 24 (36.36%) were between gestational age 34-<37 and 26 (39.39%) were ≥37 weeks of gestation. Female gender increases the chances of developing hypoglycaemia by three times [21]. In the hypoglycaemia group, adjusted analysis showed a lower fine motor function for boys, β = − 16.4, p = 0.048 [22].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, abnormal physiological manifestations or disease states of the newborn such as hypothermia, underfeeding, acidosis, intrapartum hypoxia‐ischemia, fetal distress, erythrocytosis and respiratory distress, are also considered high‐risk factors by many guidelines 2,13,15,17–20 . It was found that sepsis, respiratory distress syndrome and mechanical ventilation increased the incidence of neonatal hypoglycemia by 7‐, 5‐ and 3‐fold, respectively 28 …”
Section: Discussionmentioning
confidence: 99%
“…2,13,15,[17][18][19][20] It was found that sepsis, respiratory distress syndrome and mechanical ventilation increased the incidence of neonatal hypoglycemia by 7-, 5-and 3-fold, respectively. 28 Early initiation of breastfeeding, ≤3 h between feedings, and early mother-infant SSC are widely recognised preventive measures against neonatal hypoglycemia. The gastric emptying time in newborns is about 2 h. A feeding interval of no more than 3 h is consistent with the gastric emptying patterns in newborns.…”
Section: Cps [15]mentioning
confidence: 99%